Nutritional Supplementation to Increase Influenza Vaccine Response in Children Living With HIV: A Pilot Clinical Trial - Sainz, Talía; Casas, Inmaculada; González-Esguevillas, Mónica; Escosa-Garcia, Luis; Muñoz-Fernández, María Ángeles; Prieto, Luis; Gosalbes, María José; Jiménez-Hernández, Nuria; Ramos, José Tomas; Navarro, María Luisa; Mellado, María José; Serrano-Villar, Sergio; et al. (Frontiers in Pediatrics, 2022)
Aims: Vaccine response is poor among children living with HIV. The gut microbiota has been identified as a potential target to improve vaccine immunogenicity, but data are scarce in the context of HIV infection. Methods: Pilot, double-blind, randomized placebo-controlled trial in which 24 HIV-infected children were randomized to receive a mixture of symbiotics, omega-3/6 fatty acids, and amino acids or placebo for four weeks, each in combination with ART, and were then immunized against influenza. Vaccine response and safety of the nutritional supplementation were the primary outcomes. Results: Eighteen HIV-infected children completed the follow-up period (mean age 11.5±4.14 years, 61% female). The nutritional supplement was safe but did not enhance the response to the influenza vaccine. A fourfold rise in antibody titers was obtained in only 37.5% of participants in the intervention arm vs. 40% in the placebo. No immunological or inflammatory predictors of vaccine response were identified. Conclusions: In this exploratory study, a four-week course of symbiotics did not increase influenza vaccine immunogenicity in HIV-infected children.